Automatic Semantic Segmentation of Anatomical Structures in CT Scans - Criminisi, Antonio; Montillo, A.; Shotton, Jamie; Pathak, S.; Winn, John; Siddiqui, K. (Radiological Society of North America (RSNA), 2010)
The growing use of MDCT scans has introduced the need for radiologists to read and interpret a huge number of images in their routine workflow. An efficient, fully automatic algorithm for anatomy segmentation is introduced, which promises to improve such workflow by enabling semantic navigation and quantitative image analysis at the touch of a button.